Can South–South Cooperation Compete? The Development Bank of Latin America and the Islamic Development Bank. Issue 1 (13th January 2019) - Ray, Rebecca; Kamal, Rohini
ABSTRACT: Southern‐led multilateral development banks (MDBs) play a key role in harnessing global capital to finance the sectors most important to borrowers, especially infrastructure. Two prominent Southern MDBs, the Development Bank of Latin America (CAF) and the Islamic Development Bank (IsDB), have become crucial drivers of regional infrastructure growth. This article explores whether their performance has lived up to their goals of establishing borrower control over bank governance without sacrificing financial dynamism. Using power‐weighted voting indices for member representation on bank boards, the authors determine that these banks offer borrowers much more representation on their boards than do their Northern‐based counterparts, the Inter‐American Development Bank (IDB) and the World Bank International Bank for Reconstruction and Development (IBRD). The article also analyses bank operations to determine whether their governance structure impacts their internal performance, as reflected on balance sheets, and external performance — gaining relevance in development finance and particularly in infrastructure lending, including the burgeoning sector of sustainable (climate‐resilient) infrastructure. The authors find that the CAF and IsDB have become major players in development finance, including in sustainable infrastructure. However, important issues remain in relation to their continued internal capacity development, especially with regard to the environmental and social safeguards necessary to oversee lending.